Translating Orients : Between Ideology and Utopia - Weiss, Timothy, 1949- (Book collections on Project MUSE., 2004)
Drawing on Buddhist thought and offering, in part, a response to Edward Said's classic work in the same field, Translating Orients re-interprets Orientalism and shows the vital presence of the Orient in twentieth century and contemporary world literatures. Defining Orients as neither subjects nor objects but realities that emerge through translational acts, Timothy Weiss argues that all interpretation can be viewed as translations that contain utopian as well as ideological aspects. The translational approach to literary and cultural interpretations adds depth to Weiss's analysis of works by Jorge Luis Borges, Paul Bowles, V.S. Naipaul, Salman Rushdie, and Kazua Ishiguro, among others. Weiss examines texts that reference Asian, North African, or Middle Eastern societies and their imaginaries, and, equally important, engage questions of individual and communal identity that issue from transformative encounters. Interpretation is thus viewed as an act that orients, mapping the world not in the sense of delineating a pre-given form, location, or order, but rather as a charting of its emergence and possibilities. In addressing the principal challenges of contemporary critical thinking, fundamentalism, and groundlessness, Weiss puts forward new concepts of identity and citizenship in the reinterpretation of Orientalism.